Effect of the P-Selectin Inhibitor Crizanlizumab on Survival Free of Organ Support in Patients Hospitalized for COVID-19: A Randomized Controlled Trial - Solomon, Scott D; Lowenstein, Charles J; Bhatt, Ankeet S; Peikert, Alexander; Vardeny, Orly; Kosiborod, Mikhail N; Berger, Jeffrey S; Reynolds, Harmony R; Mavromichalis, Stephanie; Barytol, Anya; Althouse, Andrew D; Luther, James F; et al. (Circulation (New York, N.Y.), 2023)
COVID-19 has been associated with endothelial injury, resultant microvascular inflammation and thrombosis. Activated endothelial cells release and express P-selectin and von Willebrand factor, both of which are elevated in severe COVID-19 and may be implicated in the disease pathophysiology. We hypothesized that crizanlizumab, a humanized monoclonal antibody to P-selectin, would reduce morbidity and death in patients hospitalized for COVID-19. An international, adaptive, randomized controlled platform trial, funded by the National Heart, Lung, and Blood Institute, randomly assigned 422 patients hospitalized with COVID-19 with moderate or severe illness to receive either a single infusion of the P-selectin inhibitor crizanlizumab (at a dose of 5 mg/kg) plus standard of care or standard of care alone in an open-label 1:1 ratio. The primary outcome was organ support-free days, evaluated on an ordinal scale consisting of the number of days alive free of organ support through the first 21 days after trial entry. The study was stopped for futility by the data safety monitoring committee. Among 421 randomized patients with known 21-day outcomes, 163 patients (77%) randomized to the crizanlizumab plus standard-of-care arm did not require any respiratory or cardiovascular organ support compared with 169 (80%) in the standard-of-care-alone arm. The adjusted odds ratio for the effect of crizanlizumab on organ support-free days was 0.70 (95% CI, 0.43-1.16), where an odds ratio >1 indicates treatment benefit, yielding a posterior probability of futility (odds ratio <1.2) of 98% and a posterior probability of inferiority (odds ratio <1.0) of 91%. Overall, there were 37 deaths (17.5%) in the crizanlizumab arm and 27 deaths (12.8%) in the standard-of-care arm (hazard ratio, 1.33 [95% CrI, 0.85-2.21]; [probability of hazard ratio>1] = 0.879). Crizanlizumab, a P-selectin inhibitor, did not result in improvement in organ support-free days in patients hospitalized with COVID-19. URL: https://www. gov; Unique identifier: NCT04505774.